Cover Feature: A Review on Li+/H+ Exchange in Garnet Solid Electrolytes: From Instability against Humidity to Sustainable Processing in Water (ChemSusChem 20/2021). Issue 20 (29th September 2021) - Ye, Ruijie; Ihrig, Martin; Imanishi, Nobuyuki; Finsterbusch, Martin; Figgemeier, Egbert
Abstract : The Cover Feature shows the Li + /H + exchange reaction of garnet‐type solid electrolytes in contact with water/humidity, which impairs the Li + ‐conduction and necessitates the use of environmentally harmful organic solvents in the production of all‐solid‐state batteries. Fundamental understanding of this exchange reaction and subsequent engineering of thermal production processes that promote the reversed reaction enable the water‐based processing of garnet‐based separators and fluorine‐free, garnet based all‐solid‐state lithium batteries. The combination of fundamental and application‐oriented research is thus essential to build a bridge towards an environmentally friendly and sustainable production of future energy‐storage devices. More information can be found in the Minireview by R. Ye et al .